High Dose Methotrexate Treatment in Childhood ALL: Pilot Study on the Impact of the MTHFR 677C>T and 1298A>C Polymorphisms on MTX-related Toxicity - Haase, R.; Elsner, K.; Merkel, N.; Stiefel, M.; Mauz-Körholz, C.; Kramm, C. M.; Körholz, D. (Klinische Pädiatrie, 2012)
Methotrexate (MTX) is commonly administered in high doses for treatment of childhood acute lymphoblastic leukemia (ALL). The aim of this analysis was to study the influence of 2 common MTHFR polymorphisms (MTHFR 677C>T and 1298 A>C) on MTX toxicity in children with ALL.Retrospective analysis of 129 MTX courses in 34 pediatric patients with ALL.677C>T variants (CT or TT) were found in 19 (14 heterozygous, 5 homozygous) and 1298A>C variants (AC or CC) in 20 (16 heterozygous, 4 homozygous) patients. The MTHFR 677C>T wild type was associated with an increased frequency of grade III and IV leukopenia (60% vs. 31%, p<0.05) compared to the variants. The rate of severe infections (21% vs. 0%, p<0.05) and grade III–IV anemia (26% vs. 5%, p<0.05) was increased in carriers of the MTHFR 677C>T wild type compared to patients with the TT variant. Grade III–IV anemia was more frequent in patients with the MTHFR 1298A>C CC variant compared to the wild type (56% vs. 21%, p<0.05). The differences were not significant in a patient-based analysis.MTX related toxicity might be influenced by the MTHFR 677C>T or the MTHFR 1298A>C polymorphisms. Differences in MTX toxicity are only partially explainable by these 2 polymorphisms.
Keywords: methotrexate; toxicity; MTHFR; polymorphism